You need to provide an equation for this to be solved
Answer:
1/18
Step-by-step explanation:
-(-5/9) would turn into a positive 5/9. It cancels its own negative out.
The problem then turns to -1/2+5/9. Find the least common denominator and then combine.
Y directly proportional to WX and inversely to Z.
Y=k(WX)/Z
Where k is the constant of proportionality.
So, the first thing is to find the value of this constant.
k = YZ/WX
= (32×3)/(6×20)
= 96/120
= 0.8
The <span>equation that models the relationship will be;
Y = 0.8(WX/Z)</span>
F(x) = √(5x + 7)
g(x) = √(5x - 7)
(f + g)(x) = f(x) + g(x)
(f + g)(x) = √(5x + 7) + √(5x - 7)
Answer: C)
Answer:
2
Step-by-step explanation: